2020
DOI: 10.2490/prm.20200026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Native Vitamin D and Eldecalcitol on Muscular Strength and Dynamic Balance in Patients with Postmenopausal Osteoporosis

Abstract: Objectives: Previous studies have suggested that the effects of vitamin D in preventing osteoporotic fractures result in part from its influence on fall prevention. However, the effects of vitamin D on dynamic balance as a contributor to fall prevention have not been fully evaluated. Moreover, few studies have compared the effects of native and active forms of vitamin D. The objective of this preliminary randomized prospective study was to compare the effects of native vitamin D and eldecalcitol o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…We contacted the authors of those studies and obtained the required data for one of the studies ( 13 ). Five of them were changed to mean and variance for further analysis according to medium, range, or mid-quartile range and the sample size ( 14 , 15 , 17 , 19 , 20 ). Finally, we identified 12 RCTs in which active vitamin D analogues (calcitriol ( 12 , 13 , 15 , 16 , 21 ): n=5, alfacalcidol ( 14 , 17 , 18 , 22 ): n=4, eldecalcitol ( 19 , 20 , 39 ): n=3) were used ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We contacted the authors of those studies and obtained the required data for one of the studies ( 13 ). Five of them were changed to mean and variance for further analysis according to medium, range, or mid-quartile range and the sample size ( 14 , 15 , 17 , 19 , 20 ). Finally, we identified 12 RCTs in which active vitamin D analogues (calcitriol ( 12 , 13 , 15 , 16 , 21 ): n=5, alfacalcidol ( 14 , 17 , 18 , 22 ): n=4, eldecalcitol ( 19 , 20 , 39 ): n=3) were used ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the included trials reported results of falls ( 19 , 21 , 22 ). Ten of the included trials reported results of muscle strength ( 12 20 , 39 ). One of the included trials reported results of both of falls and muscle strength ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations